If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(5x + -9) = 42 Reorder the terms: 7(-9 + 5x) = 42 (-9 * 7 + 5x * 7) = 42 (-63 + 35x) = 42 Solving -63 + 35x = 42 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '63' to each side of the equation. -63 + 63 + 35x = 42 + 63 Combine like terms: -63 + 63 = 0 0 + 35x = 42 + 63 35x = 42 + 63 Combine like terms: 42 + 63 = 105 35x = 105 Divide each side by '35'. x = 3 Simplifying x = 3
| 31-[3+6y-3(y+2)]=-2(3y-5)-[7(y-1)-4y+1] | | 4t+11=4t-11 | | 6x-8x+2=4x+6 | | 35=3+5a | | 5-5x=-4x+16 | | 7x^2-5x+14x-10=0 | | (2t^2)-3t+9= | | 1-6a+3=5 | | 6x-8x+2=-3+6 | | -5(3x+4)=-95 | | 3(3x+2)=8(x-5) | | 23-6x=-21(1+8x)-5 | | 5/2=n/6 | | 25=-1/5x | | 4[4-(-9x-8)]=108x+112 | | -5(4-5y)=22y+1 | | 2h-8=h | | 22a+5=2+10 | | A/5-8=2 | | 10-14x-6-7x=7 | | 5c+14-2a=6b | | 79.49-16.7x=x | | 9z+18=8z+17 | | 40-9x=-10 | | 14-k/3=k | | x=8/2 | | 1-6a+3=4 | | 3(x+4)+6=-3 | | 6x-8x+2=-4+6 | | 25=n-33 | | 22a+5=6 | | X*X=4x |